1974
DOI: 10.1002/bjs.1800611205
|View full text |Cite
|
Sign up to set email alerts
|

The effect of posture on the gastric emptying of solid meals in normal subjects and patients after vagotomy

Abstract: SUMMARYThe effect of posture on gastric emptying of et al., 1973). Measurements of gastric emptying rates have produced conflicting results, partly because of the variable conditions under which the tests have been carried out. Variables of particular importance are the composition of the meal, the posture adopted by the subject during the test and the method of measurement. There is some evidence to suggest that liquids normally leave the stomach more rapidly than solids (Heading et al., 1971), and in dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Posture may be important, since McKelvey (1970) showed that liquids emptied more quickly after vagotomy when the patient was standing than when he lay on his left side. We have made similar observations with solid meals (Hancock, Bowen-Jones, Dixon, Testa, Dymock, and Cowley, 1974). It must be emphasized that in the present study all subjects were tested in the supine position throughout the observation period.…”
Section: Discussionsupporting
confidence: 69%
“…Posture may be important, since McKelvey (1970) showed that liquids emptied more quickly after vagotomy when the patient was standing than when he lay on his left side. We have made similar observations with solid meals (Hancock, Bowen-Jones, Dixon, Testa, Dymock, and Cowley, 1974). It must be emphasized that in the present study all subjects were tested in the supine position throughout the observation period.…”
Section: Discussionsupporting
confidence: 69%
“…Centres also differ in their imaging techniques, with patients being studied in a variety of positions. Body posture may influence pace of gastric emptying (26), though some authors have not found this (27). Different acquisition types are used, namely dynamic imaging, where gamma counts are continuously measured, or static imaging, where counts are intermittently measured.…”
Section: Discussionmentioning
confidence: 99%